La Vie de un vallet amerous (Digby 86): a dramatic monologue on the practice and pitfalls of seduction in medieval Britain – by Richard, author of the Besturné? - Burrows, D (Salerno Editrice, 2020)
Surviving in a single copy in Oxford, Bodleian Library, MS Digby 86, the poem La Vie de un vallet amerous has garnered itself a reputation for its singular obscenity, but it is arguably of greater interest in Anglo-Norman literary history for being a comic dramatic monologue composed in a distinctive verse form. The present article offers a new critical edition of the text and reflects on its relationship to the rest of the manuscript, with particular attention to its affinities to La Besturné, an Anglo-Norman nonsense poem conventionally attributed to a certain Richard.